2010
DOI: 10.1182/blood-2010-02-269878
|View full text |Cite
|
Sign up to set email alerts
|

LEF-1 is a prosurvival factor in chronic lymphocytic leukemia and is expressed in the preleukemic state of monoclonal B-cell lymphocytosis

Abstract: The canonical Wnt signaling pathway is pathogenic in a variety of cancers. We previously identified aberrant expression of the Wnt pathway transcription factor and target gene lymphoid enhancer binding factor-1 (LEF1) in chronic lymphocytic leukemia (CLL). This suggested that the Wnt signaling pathway has a role in the biology of CLL. In this study, we performed a Wnt pathway analysis using gene expression profiling and iden-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
149
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 31 publications
14
149
0
Order By: Relevance
“…16,17 A recent study demonstrated that LEF1 is not only overexpressed in chronic lymphocytic leukemia/small lymphocytic lymphoma, but also in its preleukemic state of monotypic B lymphocytosis. 7 These findings suggest that LEF1 may have a role in the pathogenesis of chronic lymphocytic leukemia.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…16,17 A recent study demonstrated that LEF1 is not only overexpressed in chronic lymphocytic leukemia/small lymphocytic lymphoma, but also in its preleukemic state of monotypic B lymphocytosis. 7 These findings suggest that LEF1 may have a role in the pathogenesis of chronic lymphocytic leukemia.…”
mentioning
confidence: 75%
“…16,17 A recent study shows that LEF1 is not only overexpressed in chronic lymphocytic leukemia, but also in the CD5 þ /CD19 þ cells from patients with monoclonal B-cell lymphocytosis, suggesting a role of LEF1 in early leukemogenesis of chronic lymphocytic leukemia. 7 So far, the data on LEF1 expression in B-cell lymphoma are limited, and the evaluation has been through molecular or other methods primarily used in research settings. Our study assessed LEF1 expression by immunohistochemistry in a large series of chronic lymphocytic leukemia/small lymphocytic lymphoma as well as other types of B-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, LEF-1 was found to be one of critical transcription factors for the activity of Crlz1 promoter. As LEF-1 has been reported to be expressed stage-specifically from pro-B to pre-B cells during B cell development (Gutierrez et al, 2010;Reya et al, 2000) and play a role to open its target chromatin with β-catenin in the Wnt (wingless-type MMTV integration site) signaling pathway (Heo et al, 2010;Mosimann et al, 2009), the involvement of LEF-1 in the regulation of Crlz1 promoter activity could provide a potential explanation for the molecular mechanism for the pre-B cell stage-specific activity of Crlz1 promoter, i.e., for the pre-B cell stage-specific histone hyperacetylation and chromatin opening of Crlz1 promoter and thereby its subsequent gene expression (Lim et al, 2006). Therefore, it is possible that the initial binding of pre-B cell stage-specific LEF-1 to the distal region of Crlz1 promoter might open the promoter chromatin to start to activate the promoter specifically in the pre-B cell stage, while multiple bindings of relatively ubiquitous Ets family members such as Fli-1 and GABP to its proximal region might further amplify the Crlz1 promoter activity by multiple additive interactions.…”
Section: Discussionmentioning
confidence: 99%